Aksi dan Kontemplasi: Menyikapi Peran Marta dan Maria Perspektif Injil Lukas 10:38-42 dan Relevansi bagi Kaum Muda - Fladimir Sie; Siprianus Soleman Senda (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This article analyzes the roles of Mary and Martha from the perspective of Luke 10:38-42, which depicts two different attitudes in welcoming the arrival of Jesus: action (Martha) and contemplation (Mary). This research aims to analyze the differences between these two attitudes and how they can be applied in the lives of today's youth. Using a literature review method, this study examines the importance of action and contemplation in the spiritual and daily lives of young people. The results of the study show that these two attitudes complement each other. Both have strong relevance in providing guidance for the younger generation to achieve a balance between dynamic social activity and deep spiritual experience. This offers important insight into how young people can find harmony in a life full of demands and challenges while maintaining their closeness to God.